Learning in current times, technology, emotions, pandemic (Research, Society and Development, 2022)
Studies and transformations over the years in the academic environment, innovative paths in the methodological process for learning, understanding that medicine, technology, education can go together, creating a better world. The impact that diseases have transformed the social, political, psychological, understanding of anxieties and fears qualifying for a better future. Technologies have created a new online classroom environment, a new teacher and student moment, new teaching opportunities, some enjoying and others not having opportunity and access. How to be able to control emotions in the face of a new virus and so many sudden changes in the learning process.